Heist Artist - Vish Dhamija (Noida, Uttar Pradesh HarperCollins Publishers, 2019)
Vagh Pratap Singh aka the Captain is a conman extraordinaire. From transporting illegal merchandise and stealing cars to breaking safes, he's done it all. But now, in his fortieth year, he's ready to retire. So when Udham Kumar, a crooked politician from Uttar Pradesh, commissions the Captain to track down and steal Poppy Flowers, a Vincent van Gogh's painting that has been smuggled into India after it went missing in a museum in Egypt in 2010, the Captain knows that he's found his last, and biggest case. But the painting is now in possession of a dangerous gangster, and the Captain is being followed by Udham Kumar's ruthless associates, greedy for both money and power. As the odds against him begin to stack up, the Captain realizes that his last heist might not be as easy as he'd imagined.
Keywords: Drawing and Drawings